Resirkulasi Air Untuk Optimalisasi Kualitas Air Budidaya Ikan Nila Nirwana (Oreochromis niloticus) - Safira Rahma Fauzia; Sugeng Heri Suseno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Water is a living medium of aquatic organisms. Water plays an important role in aquaculture. Good water quality will determine the survival of the fish being cultivated. Recirculation is an effort to maintain water quality and overcome water problems in the Sukadamai Village aquaculture pond. This activity was carried out in RW 4 of Sukadamai Village, Dramaga District, Bogor Regency which aims to analyze the potential of fisheries in the Sukadamai Village aquaculture pond, the use of recirculation to maintain water quality. This activity was carried out on Friday, February 28, 2020 in the House of Pak Nadi RW 4, Sukadamai Village, Dramaga District, Bogor Regency, West Java. The data collection method is by interview and analyzed descriptively. The results of this activity found that the quality of the waters in the Sukadamai Village aquaculture pond was quite good because it directly used natural springs. Recirculation can be used to overcome the problem of far springs from the location of cultivation so that water can be reused. The use of filters can optimize the recirculation system in the Sukadamai Village aquaculture pond. The conclusion is that the problem of water quality is not too felt by farmers in Sukadamai Village. Keywords: resirculation, tilapia, water quality